Species composition of First Nation whaling hunts in the Clayoquot Sound region of Vancouver Island as estimated through genetic analyses. (February 2018) - Béland, Stephanie L.; McLeod, Brenna A.; Martin, Joe; Martin, Gisele M.; Darling, James D.; Frasier, Timothy R.
Abstract: Deepening our understanding of whale hunting practices is important from both cultural and biological perspectives. Many cultures practice whaling activities, including the Nuu-cha-nulth Nations of the Pacific Northwest. Nuu-cha-nulth cultural lifeways and laws include great care and respect for these animals that provide so much wealth to their communities. The disruption of this culture by colonial governments, combined with the decimation of whale populations through industrial whaling, led to the loss of traditional whaling activities and a gap between contemporary and historical knowledge and practices. From a scientific perspective, knowledge of current whale populations is compromised by lack of data with regards to abundance and distribution of these populations prior to colonial industrial whaling. Analysis of whale bones from First Nation whaling sites are valuable for addressing both these issues by identifying the species landed by communities in traditional hunts, and by providing a sample of the presence and distribution of whale species before colonial industrial whaling. Genetic analyses of 95 bones collected from 7 traditional whaling sites of Nuu-chah-nulth First Nations in the Pacific Northwest were conducted, as well as 11 bones from a colonial industrial whaling site in the area that operated from 1905 to 1918. Specifically, we sequenced a portion of the mitochondrial control region and cytochrome-b gene to identify what species were taken, and in what proportions. We found that 45.4% of the bones were from grey whales ( Eschrictius robustus ), 43.0% were from humpback whales ( Megaptera novaeangliae ), 8.1% were from North Pacific right whales ( Eubalaena japonica ), and the remaining 3.5% were from fin whales ( Balaenoptera physalus ). These results reveal catch compositions of historical hunts, and therefore help to inform our understanding of historic practices and preferences, and provide information on which species were present in these areas. Highlights: Genetic analyses identified species composition at historical whaling sites. Composition at sites was primarily grey (45.4%) and humpback (43.0%) whales. Other species also found: North Pacific right whales (8.1%), fin whales (3.5%). Provides information on past species occurrence and exploitation in the area. Provides reference samples against which contemporary samples can be compared.